THE IMPORTANCE OF USING CIRCUIT TRAINING IN PERFORMANCE ATHLETES - Enea(căs. Ungureanu)Laura Cristina (Sport şi Societate)
We can see that in the last 30 years, performance athletes have become better and better physically prepared, regardless of the sports branch to which they belong. Tennis is no exception to this trend, meeting in professional circuits players with impressive physical features both visually and through the biomechanics of movements. At the same time, these physical qualities were not acquired overnight, but were rigorously practiced from the initiation in the game of tennis. Over the years, a number of physical training methods have emerged that aimed to improve the game of tennis by increasing physical performance.The present research aims to verify the increase in individual physical performance of young tennis players following the implementation of a circuit-type training program. In the research we included 5 subjects, tennis players at competitive level, aged between 11 and 16 years. They were tested in two tests 6 weeks apart, before and after thetraining program. Following the tests carried out, we identified significant progress obtained by the subjects in the physical tests.